Estudio de las marcas de propiedad de miembros de la Casa de Borbón entre los siglos xvii y xix en la Biblioteca de la Casa de Velázquez - Antonio Carpallo Bautista; José María de Francisco Olmos; Yolanda Isabel Bustamante Sampedro (Mélanges de la Casa de Velázquez)
Bindings with heraldic superlibros are characterised by the main decorative motif of the coat of arms of their former owners, making them one of the best examples of the potential of bookbindings as a documentary source. To this value as a historical document must be added the enormous variety of decorative and constructive techniques, as well as materials, that make up these bindings and that make them authentic functional works of art. Heraldic bindings are a testimony of the lives of their owners and in them are observed the distinctions that are awarded, orders and decorations, in addition to observing the aesthetic tastes and techniques available at the time of their execution. They are, therefore, a historical, artistic and technological heritage. In this work, the bindings with heraldic superlibros of members of the House of Bourbon and their dynastic links and of the city of Rouen are studied.